2011
DOI: 10.1097/dbp.0b013e31821102ee
|View full text |Cite
|
Sign up to set email alerts
|

Sense of Coherence as a Predictor of Quality of Life in Adolescents With Congenital Heart Defects: A Register-Based 1-Year Follow-Up Study

Abstract: SOC is an independent predictor of QoL in adolescents with CHD. In psychological well-being, this prediction remains stable, whereas in total well-being and all other QoL subdimensions, its strength as such wanes over the course of a year but does not entirely dissipate. Further studies should evaluate whether interventions designed to increase SOC in children with CHD would also improve their QoL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 53 publications
4
27
0
Order By: Relevance
“…Two key temporal sequences involving SOC were uncovered. In line with our hypotheses, SOC was found to be an over time predictor of quality of life [35]. Growing up with CHD has been hypothesized to influence positively the development of SOC for some individuals, partially because these patients have learned to cope with CHD (manageability) and having CHD often has high existential implications (meaningfulness) [36].…”
Section: Discussionsupporting
confidence: 70%
“…Two key temporal sequences involving SOC were uncovered. In line with our hypotheses, SOC was found to be an over time predictor of quality of life [35]. Growing up with CHD has been hypothesized to influence positively the development of SOC for some individuals, partially because these patients have learned to cope with CHD (manageability) and having CHD often has high existential implications (meaningfulness) [36].…”
Section: Discussionsupporting
confidence: 70%
“…Using the SOC-13 questionnaire, they assessed the sense of coherence in 429 young people with CHD (14-18 years), and found that higher sense of coherence scores and better physical health explained better quality of life in patients, compared to healthy controls ; and that sense of coherence at time 1, in a longitudinal study over a 9-month period predicted several domains of general and disease-specific perceived health at time 2 . Positive associations between the sense of coherence scores and quality of life measures were evidenced also in other samples of adolescents with CHD, for instance in Japan, in a sample of 172 adolescents aged 12-18 (Nio, 2010); in Australia, in a sample of 114 patients aged 12-20 (Wang, Hay, Clarke, & Menahem, 2014); or in Germany, in a sample of 770 adolescents aged 14-17 (Neuner et al, 2011). The SOC-13 questionnaire was used in all of these studies, except for Neuner et al's study, where the sense of coherence was measured with a shortened version, the SOC-L9 questionnaire (Schumacher, Wilz, Gunzelmann, & Brahler, 2000).…”
Section: Sense Of Coherence In Relation To General Health Behaviorsmentioning
confidence: 91%
“…Accordingly, results of various studies showed that adolescents with higher SOC reported a more healthy life style, a better quality of life, and wellbeing (Honkinen et al, 2009;Neuner et al, 2011). The healthy lifestyle related on one hand to physical activities and exercises (Bronikowski, 2010) and on the other hand to smoking habits, alcohol abuse , 2013aMyrin & Lagerström, 2006;Nielsen & Hansson, 2007), and eating habits (Myrin & Lagerström, 2006).…”
Section: Soc Health Mental Health and Psychosocial Behaviormentioning
confidence: 99%
“…A second limitation is that other variables, which were not addressed in this study, might have influenced the subjective QoL of these adolescents, besides being discharged from secure residential care. Others, for instance, have found that sense of coherence is associated with subjective well-being (Moksnes et al, 2013;Neuner et al, 2011;Oztekin & Tezer, 2009). …”
Section: Limitationsmentioning
confidence: 94%